MENINGKATKAN KEMAMPUAN DAN KUALITAS VISUALISASI DATA KARYA ILMIAH MAHASISWA MELALUI PELATIHAN DAN PENDAMPINGAN INTENSIF - Akbar, Paisal; Fahlevy, Muhammad Reza; Irawan, Bambang; Fourqoniah, Finnah; Budiman, Budiman; Rohmah, Ainun Nimatu; Arieyasmieta, Wildan Lutfi (An-Nizam, 2025)
The training and mentoring program for data visualization of scientific papers by students from the Faculty of Social and Political Sciences at Universitas Mulawarman aims to enhance students' skills in processing and presenting research data effectively. This activity was motivated by the need to support reputable scientific publications, thereby strengthening study program accreditation and addressing the challenge of low scientific journal productivity in the academic environment. The training was conducted over five weeks, from October to November 2024, combining classical and non-classical face-to-face methods. The training materials covered software such as Microsoft Excel, Publish or Perish, and VOSviewer, with a focus on software installation, data processing, and research-based visualization. Evaluation was conducted through analysis of participant participation and responses. The training results demonstrated high participant enthusiasm, with 424 students participating. Most participants responded positively, noting the activities and their benefits in supporting their academic pursuits. The results of this community service demonstrate the training's success in improving student competency, supporting scientific publication productivity, and strengthening efforts to improve study program accreditation.